Mineralogy and geochemistry of the Cambrain Shuijingtuo Formation black shales from Western Hubei, China: implications on enrichment of critical metals and paleoenvironment - Wang, Yuan; Li, Jing; Lin, Yang; Zhuang, Xinguo; Hoang, Vanlong; Wu, Peng; Luo, Xin; Zhang, Han; Zhang, Xiaoyang (Frontiers in Marine Science, 2024)
Black shales have attracted the attention of numerous researchers not only due to their high potential as hydrocarbon source rocks and shale gas reservoirs, but also to the enrichment of critical metal elements in black shale series. Black shale of the Cambrian Shuijingtuo Formation is one of the most important black shales in the Yangtze platform. This paper conducts integrated research on the mineralogical and geochemical characteristics of this black shale from the Luojiacun section in Western Hubei Region, aiming at elaborating the enrichment mechanism of elevated critical metal elements in the Shuijingtuo black shale. Minerals in the Shuijingtuo black shale are predominantly composed of quartz (avg. 43.0%) and clay minerals (avg. 32.5%), with small proportions of calcite, albite, clinochlore, and pyrite. The Shuijingtuo black shale is characterized by high total organic carbon (TOC, avg. 3.9%) content and enriched in V-Ni-Cr-U and Sr-Ba critical metal assemblages. The elevated V, Cr, Ni, and U present dominant organic affinities, while Sr and Ba are closely correlated to calcite and pyrite, respectively. The enrichment of V-Cr-Ni-U critical element assemblages in Shuijingtuo black shale are ascribed to the high primary productivity, anoxic depositional conditions, marine biologic production, and low-temperature hydrothermal activities. The enrichment of Sr and Ba is related to the high primary productivity and anoxic depositional conditions, respectively.